1993
DOI: 10.1111/j.1151-2916.1993.tb04033.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion Discontinuities of Mullite

Abstract: Thermal expansion data of mullite were collected between 25" and 800°C with high accuracy by means of an X-ray high-temperature Guinier powder camera, and high-resolution single-crystal Bond techniques. 3/2-type mullites, synthesized from chemically coprecipitated precursors and 2/1-type fused-mullite single crystals, were used for the measurements. Mullite displays low and nonlinear thermal expansions along the crystallographic a, b, and c axes below about 200"C, and linear expansions between 200" and 400°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Mullite phase emerged at not less than 1200 • C through silica and alumina reaction while it arose at more than about 1000 • C in the phase transformation of kaolin [6,7]. The temperature of mullite formation dropped to 750 • C in the transformation of kaolin loaded with a suitable amount of vanadium, which showed that vanadium reacted significantly with kaolin.…”
Section: Chemical Interaction Of Kaolin-vanadiummentioning
confidence: 88%
See 1 more Smart Citation
“…Mullite phase emerged at not less than 1200 • C through silica and alumina reaction while it arose at more than about 1000 • C in the phase transformation of kaolin [6,7]. The temperature of mullite formation dropped to 750 • C in the transformation of kaolin loaded with a suitable amount of vanadium, which showed that vanadium reacted significantly with kaolin.…”
Section: Chemical Interaction Of Kaolin-vanadiummentioning
confidence: 88%
“…Mullite formation through kaolin phase transformation had been investigated early [7], while the process of low temperature phase transformation by addition of vanadium has not yet been found in the literature. The effect of vanadium load on mullite content formed through kaolin transformation is shown in Fig.…”
Section: Process Of Mullite Formationmentioning
confidence: 99%
“…For pure 2:1 fused-mullite (x = 0.40), thermal expansion along the c-axis was greatest followed by b and a. Further studies (Schneider et al 1993) indicated that mullites displayed discontinuities in thermal expansion between about 400 and 500 °C. Expansion discontinuties were large along a, but much smaller along b and c. The slopes of a-and volume-expansion curves, respectively, were steeper above the expansion discontinuity than below it, but this tendency was not observed for those of b and c. It was supposed that such behavior in thermal expansion possibly could be caused by deformation, rotation, or tilting of the AlO 6 octahedra, or by deformation of T*O 4 tetrahedra of the mullite structure.…”
Section: Introductionmentioning
confidence: 87%
“…Mullite (3Al 2 O 3 ·2SiO 2 ), as the only binary compound in the SiO 2 -Al 2 O 3 system [1], is a promising material for advanced structural and refractory ceramic because of its promising thermo-mechanical properties such as low thermal expansion, low thermal conductivity, excellent creep resistance, good chemical properties and oxidation resistance [2][3][4][5][6][7]. Recently, considerable work has been done to characterize the composition and microstructure of mullite [8].…”
Section: Introductionmentioning
confidence: 99%